What is and how do we Achieve a Resilient Digital Democracy? - Fuchs, Christian (Open Research Europe)
This paper develops a new concept and framework for understanding resilient digital democracy in an age defined by polarisation, cascading crises, and the global rise of digital authoritarianism. It begins by tracing the concept of resilience from systems theory to social and political life, showing that resilience in democracy is not a mechanical property of systems but a dynamic, human-driven practice grounded in agency, resistance, and collective self-determination. The paper argues that with emerging challenges in the digital sphere, such as misinformation, surveillance capitalism, platform monopolies, deepfakes, and hybrid warfare, democracy can only endure if its digital dimensions are protected and transformed. Building on this foundation, the paper introduces a holistic approach to resilient digital democracy that spans environmental, technological, economic, political, and cultural domains, and advances strategies such as public-commons digital infrastructures, platform co-operatives, public service Internet platforms, free/libre open source software (FLOSS), participatory innovations, and hybrid offline/online democratic practices. The result is a fresh, interdisciplinary vision of how democracy can be reinvented in the digital age.

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Investigation on manufacturing-induced pre-deformation on the fatigue behaviour of clinched joints - Schlichter, Malte Christian; Harabati, Özcan; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
The present study is an experimental analysis of the influence of pre-forming on the failure behaviour of clinched specimens under quasi-static and cyclic loading conditions. In this context, the geometric formation of the clinched joints is taken into account, with regard to the loading behaviour. The study also includes a comparison of the failure behaviour of quasi-static and cyclic tested specimen. Testing is done on non-pre-deformed and pre-deformed specimens. For this purpose, experimental investigations are carried out on two material combinations consisting of HCT590X steel sheet and EN AW-6014 T4 aluminium sheet. The focus is on the fatigue analysis of the clinched joints. The aim is to identify the failure modes under cyclic loading and the crack formation with regard to forming operations prior to the joining process. The investigations show that the cyclic load-bearing behaviour of the HCT590X joints is reduced by introducing a plastic pre-deformation of the to be joined parts.

High-cycle fatigue testing and parameter identification for numerical simulation of aluminum alloy EN AW-6014 - Chen, Chin; Schlichter, Malte Christian; Harzheim, Sven; Hofmann, Martin; Bobbert, Mathias; Meschut, Gerson; Wallmersperger, Thomas (Materials Research Proceedings)
Abstract. As a widely used sheet metal in clinched joints within the automotive industry, the aluminum alloy EN AW-6014 has been the focus of numerous studies. High-cycle fatigue (HCF) is a critical aspect when assessing the durability of clinched joints. In the present work, the HCF behavior of EN AW-6014 T4 was explored both experimentally and numerically. To model the fatigue behavior, Lemaitre’s two-scale damage model was used. Two key parameters, damage strength and damage exponent, are necessary for numerical investigations of HCF behavior. These parameters were determined through experiments with flat specimens and subsequently validated within a numerical model of clinched joints. The numerical results for fatigue match the experimental ones of the clinched joints quite well.

Cross-process damage modeling: A process-chain case study of clinching and self-pierced riveting for aluminum connections - Harabati, Özcan; Bielak, Christian Roman; Böhnke, Max; Schlichter, Malte Christian; Brockmeier, Marc; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
This study focuses on damage modeling across different mechanical joining processes within a process chain, specifically using clinching and self-pierce riveting (SPR). The aim is to apply a comprehensive model that captures the damage mechanisms and interactions in these technologies, optimizing them for enhanced performance and durability of aluminum joints. A GISSMO damage model was utilized, based on the stress states occurring during the joining process and a newly introduced damage testing method. This model was applied to both clinching and SPR processes. A detailed analysis of the stress states provided insights into their effect on the material. By incorporating these insights into the GISSMO model, improved accuracy in damage prediction was achieved. The model's application to clinching and SPR demonstrated its effectiveness in optimizing aluminum joint performance and durability, ensuring that the processes can be finely tuned to minimize damage and enhance joint quality.

Application of stress-state-dependent ductile damage and failure model to clinch joining for a wide range of tool and material combinations - Friedlein, Johannes; Lüder, Stephan; Kalich, Jan; Schmale, Hans Christian; Böhnke, Max; Schlichter, Malte Christian; Bobbert, Mathias; Meschut, Gerson; Steinmann, Paul; Mergheim, Julia (Journal of Advanced Joining Processes)

Simulation of the joining process of graded hardened multi-range capable rivets - Holtkamp, Pia Katharina; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
The versatile self-pierce riveting (V-SPR) is a further development of semi-tubular self-pierce riveting. V-SPR enables adaptation to changing boundary conditions, such as a change in the material thickness combination, without varying the rivet die combination due to increased punch actuation and the use of multi-range capable rivets [1]. The inner punch first sets the rivet. The outer punch then forms the rivet head to the respective sheet thickness. For this, the rivet requires a hard shank and a ductile rivet head, which is achieved by an inductive local hardening process [2]. Until now, the joint formation of rivets with graded hardness profile has been challenging to estimate in the FEM simulation due to the inhomogeneous material conditions in the rivet. In this study, a method capable of reproducing the experimentally determined hardness levels of rivets in detail is shown. This FE model enables the realistic modelling of the mechanical properties of the rivet on the basis of the hardness profile in order to predict the correct deformation processes and stresses during the riveting process. First, the detailed experimental hardness mapping of the locally heat-treated rivets is transferred into the FE model. The FEM material model can predict the local strength of the rivet based on hardness by scaling the flow curves. To estimate the predictive capability of the FEM model, the joint formation of rivets with different graded hardness profiles is compared experimentally and simulative. Based on the validated model, the influence of different rivet hardness profiles on the joint formation is analysed numerically. By adapting the material model, a high level of correlation between the experiment's joint formation and the simulation can be achieved.

In situ CT unter Temperatur: Thermokammer für thermoplastische FKV-Fügeprozesse - Dargel, Alrik; Köhler, Daniel; Gude, Maik; Kupfer, Robert (Tagungsband 43. Vortrags- und Diskussionstagung Werkstoffprüfung 2025)
Für das Verständnis und die Weiterentwicklung temperaturgestützter mechanischer Fü-geprozesse mit thermoplastischen Faser-Kunststoff-Verbunden (FKV) ist die zerstörungsfreie Analyse der Materialstruktur im Inneren des Fügepunktes während der Entstehung und Belastung erforderlich. Die Kombination aus Prüfung unter Temperatureinfluss und in situ Computertomographie (CT) eröffnet neue Möglichkeiten für die Fügeprozessanalyse. Dazu wurde dazu eine Thermokammer entwickelt und in eine bestehende in situ CT-Anlage integriert. Anwendungsszenarien sind die Herstellung und Prüfung von Fügepunkten unter Temperatur. Die Erwärmung erfolgt über einzeln regelbare Heizzonen, welche eine gezielte Temperaturführung über die gesamte Probengeometrie ermöglichen. Die Temperaturkurve eines Aufheizversuchs, sowie eine Röntgenprojektion einer Probe innerhalb der Thermokammer validie-ren die Konstruktion.
Keywords: in situ CT; Thermokammer; Thermoplastische FKV

In Situ CT of Clinch Points – Enhancing Interface Detectability Using Electroplated Patterns of Radiopaque Materials - Köhler, Daniel; Dargel, Alrik; Troschitz, Juliane; Gude, Maik; Kupfer, Robert (Journal of Nondestructive Evaluation)
Abstract A clinch point’s quality is usually assessed using ex situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In situ methods such as the force-displacement evaluation are used to investigate a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in situ computed tomography (in situ CT). When investigating the clinching of aluminum parts in in situ CT, the sheet-sheet interface is hardly visible. Earlier investigations showed that radiopaque materials can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. However, the layers cause strong artefacts, break during the clinching process or change the clinch joint’s properties significantly. In this paper, a minimally invasive method to enhance the interface detectability is presented. First, the aluminum oxide layer is removed by etching. Second, the specimen is electroplated with copper or gold, respectively. In some cases, a mask is applied to create a cross-shaped plating pattern. Then, the plated specimen is clinched with a non-plated counterpart and the interface detectability of the clinch points is assessed in CT scans. It is shown that a copper plating of 2.6–4 μm can visualize some parts of the interface, while 7–9 μm is suitable to enhance the detectability of the sheet-sheet interface almost continuously.

Numerical investigation of the effects of pitting corrosion on high-cycle fatigue of clinched joints - Chen, Chin; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Abstract The effects of corrosion on clinched joints are not completely understood yet. Recent research indicates that galvanic corrosion can actually enhance the fatigue life of clinched joints. It is then of significant interest to investigate the effects of another corrosion phenomenon, pitting corrosion, on the fatigue behavior of clinched joints. Pitting corrosion occurs in passive metals and can lead to stress concentrations. In the present study, the effects of pitting corrosion are investigated by using Lemaitre’s two-scale fatigue model with a 2D geometry of clinched joints. A slip condition is applied as a boundary condition to simplify the clinched joint model and reduce the computational cost of solving the contact mechanics problem. Additionally, a method to determine the damage strength and the damage exponent used in the two-scale damage model is introduced. Numerical simulations reveal that pitting corrosion reduces the fatigue life of clinched joints, particularly when it occurs on the internal surface in the neck area.

Numerical investigation of pitting corrosion in clinched joints - Harzheim, Sven; Chen, Chin; Hollmer, Katharina; Hofmann, Martin; Zimmermann, Martina; Wallmersperger, Thomas (Acta Mechanica)
Abstract The effect of corrosion on mechanically joined components is not well understood. While recent research shows that a brief exposure of clinched specimens to a salt spray environment improves the specimens’ fatigue life, other research shows a decrease in load bearing capabilities with increasing corrosion times. These studies primarily focus on galvanic corrosion. It is not entirely clear how other corrosion phenomena, such as pitting corrosion, affect the fatigue life of clinched joints. In this work, a numerical model is used, which is able to simulate corrosion pit growth in EN AW-6014. The experimental polarization data of EN AW-6014 are used directly in the calculation of the interface kinetics parameter of the model.

Influence of dispersion gas flow on the spray characteristics and γ-Fe2O3 nanoparticles formation and properties in reference SpraySyn burners - Massopo, Orlando; Tischendorf, Ricardo; Gonchikzhapov, Munko; Kasper, Tina; Augustin, Peter; Özer, Burak; Reddemann, Manuel; Kneer, Reinhold; Sheikh, Mohammed-Ali; Mert, Aydan Akyildiz; Wiggers, Hartmut; Schmid, Hans-Joachim (Powder Technology)
This study investigates the effect of dispersion gas (DG) flow on the formation and properties of maghemite (γ-Fe2O3) nanoparticles using standardized SpraySyn burners (SS1 and SS2). Several diagnostics were employed to characterize the spray and nanoparticles. Increasing DG flow (6 - 12 slm) results in smaller droplet sizes (DS), cooler flame temperatures, shorter high-temperature droplet/particle residence times, and smaller agglomerates in the size range of 5 - 12 nm with narrower primary particle size distribution, corresponding to higher mass fractal dimensions, as supported by TEM and SMPS analysis, resulting in more compact agglomerates. BET and TEM confirmed decreasing primary particle sizes with increasing DG flow. Raman and XRD analyses predominantly identified maghemite, which shows a bimodal distribution of crystallite sizes, while SS1 samples have a greater proportion of larger crystallites. The self-preserving size distributions of agglomerates with a geometric standard deviation of 1.5 are reached faster with increasing DG flow. The barrier effect of DG observed in SS1 leads to slower droplet combustion kinetics, higher temperatures, and delayed precursor release, which, along with downstream flow recirculation, result in significantly higher agglomeration rates outside the visible flame. SS2 demonstrates improved atomization, more stable flames, and finer, uniform nanoparticles with less carbonaceous residues (CR). Conversely, SS1 showed broader DS distributions and higher CR levels on the γ-Fe2O3 surface, especially at higher DG flow. This work highlights the essential role of DG flow and nozzle geometry in controlling droplet evaporation, flame stability, and nanoparticle growth, offering insights for optimizing SFS and validating numerical models.
Keywords: Spray flame synthesis; iron oxide nanoparticle; SpraySyn burner; Dispersion gas; Coaxial atomization; HiaT-SMPS

Quantitative holography for the characterisation of semiconductor amplifieres and lasers - Gerhardt, Nils Christopher; Hofmann, Martin R.; Zens, Leon; Möller, Jens; Besaga, Vira (Practical Holography XXXIX: Displays, Materials, and Applications)

Nontrivial $t$-designs in polar spaces exist for all $t$ - Weiß, Charlene (Des. Codes Cryptogr.)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space over $\mathbb{F}_q$ equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-$(n,k,λ)$ design in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $k$-spaces such that each totally isotropic $t$-space is contained in exactly $λ$ members of $Y$. Nontrivial examples are currently only known for $t≤ 2$. We show that $t$-$(n,k,λ)$ designs in polar spaces exist for all $t$ and $q$ provided that $k>\frac{21}{2}t$ and $n$ is sufficiently large enough. The proof is based on a probabilistic method by Kuperberg, Lovett, and Peled, and it is thus nonconstructive.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, N. C.; Hofmann, M. R. (Journal of Applied Physics)

Efficient Online Automated Algorithm Selection in the Face of Data-Drift in Optimisation Problem Instances - Rook, Jeroen; Renau, Quentin; Trautmann, Heike; Hart, Emma (Proceedings of the 18th ACM/SIGEVO Conference on Foundations of Genetic Algorithms, FOGA 2025, Leiden, The Netherlands, August 27-29, 2025)

Die Möglichkeiten der Filament Extension Atomization - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Flow around Particles in Uniaxially Elongated Capillary Bridges - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Fließverhalten von unterschiedlichen Fluiden im Filament Extension Atomizer - Neudorf, Julian; Neukötter, Moritz